PROFIL PENGETAHUAN PASIEN TENTANG PENGGUNAAN ALLOPURINOL DI APOTEK ARDA FARMA SUKODONO - Adinugraha Amarullah; Muhamad Aulia Putra Tawakal; Farida Anwari; Pandian Yoga Fitriajeng (Jurnal Farmasi IKIFA, 2024)
Gout or commonly known as gout arthritis is a disease caused by a buildup of uric acid crystals in the body. Normal uric acid levels are below 7 mg/dl in men and below 6 mg/dl in women. Allopurinol is a gout drug that is classified as a Pharmacy Compulsory Drug (OWA). Aspects of drug therapy must be conveyed to consumers because it relates to the treatment being carried out and includes treatment goals, drug use, drug contraindications, side effects, drug interactions, method of treatment, drug storage and drug shelf life. Communicating aspects of pharmacotherapy that need attention so that consumers truly understand the information provided by pharmacists. This study aims to determine the patient's knowledge about the use of Allopurinol. The research method used is descriptive quantitative. Samples were taken based on inclusion and exclusion criteria. The number of samples used was 60 respondents. Sampling was done by purposive sampling. Based on the results of the study, patients with a sufficient level of knowledge were 47%, followed by a good category of 33% and people with a low level of knowledge of 20%. It can be concluded that the level of patient knowledge about allopurinol at Arda Farma Sukodono Pharmacy is mostly the level of knowledge is sufficient. It is hoped that it can provide education and information to the public regarding matters related to allopurinol drugs such as indications, rules for use and others. So as to prevent the use of drugs that are not rational.